Integration Measures in Communities as a Way to National Unity, Cohesion and Ensuring the National Country Interests - Trubavina, Iryna; Cherednychenko, Oleksandr; Oliinyk, Nadiia (Educational Challenges, 2024)
The article is devoted to the issue of national patriotism education in the conditions of war as a new form of social work and education for children and adults in communities. This new form is in demand in practice, with donors, but there is no theoretical justification and methodological support for it. The purpose of the article is to define a more structured, scientifically based concept of integration of internally displaced persons in social work in various state and non-state institutions, communities, definition of its logic, forms, types, requirements and recommendations to implementation. The research methods are theoretical analysis of sources, generalization of experience, induction, deduction, synthesis, observation, comparison and analysis of situations. Research methodology make up the approaches of different levels as well: philosophical, general scientific, specific scientific approaches, scientific approaches within individual sciences. The scientific novelty of the article is defining the integration measures as a new form of national-patriotic education for adults and children in the conditions of war, the method of their implementation in communities, their features as a form of educational organization and a social form work at the same time. The practical significance lies in determining the stages and recommendations for the methodology of carrying out integration activities. The results of the research are justification of the purpose, principles, content, methods and forms of integration activities, requirements for carrying them out. The prospects for further research are the generalization of experience conducting such events in Ukraine, and identifying their impact on integration of internally displaced persons in new communities. The conclusion is that the integration of people with various signs of vulnerability in Ukraine in conditions of mass resettlement and large-scale aggression is absolutely necessary.